Investigating the Effect of Renewable and Non-Renewable Energy on Air Pollution in Iran with regard to the Moderating Role of Economic Growth - sadegh imandoust; Mohammad Lashkary; Ehsan Sayyahzadeh kakhki (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2020)
Energy consumption in the world is increasing for economic growth, and as a result of the emission of greenhouse gases, especially carbon dioxide, which has destructive environmental effects, the consumption of fossil fuels has an increasing trend. Present study tries to find the effect of renewable and non-renewable energy consumption on air pollution with respect to the moderating role of economic growth, utilizing the data of time series from 1990 to 2017 in Iran and with the generalized method of moments and in terms of some control variables such as energy efficiency coefficient and urbanization, the hypotheses were tested. Findings indicate that, the effect of renewable energy consumption in reducing carbon dioxide emissions (negative coefficient at a significant level of 10%) and the effect of non-renewable energy consumption in increasing carbon dioxide emissions (positive coefficient at a significant level of 5%). Also, the role of economic growth as a moderating variable on the relationship between renewable energy consumption and carbon dioxide emissions is positive and on the relationship between non-renewable energy consumption and carbon dioxide emissions is negative and significant. Developing investment and increasing the share of the renewable energy sector in the country along with improving energy efficiency and technology level can be effective in reducing air pollution.